A case study of the effect of Ni substitution on the sintering behaviours of Ba0.5Sr0.5Co0.8Fe0.2O3−δ oxygen transport membranes. (4th July 2018) - Wang, Li; Chen, Ying; Wang, Gong; Li, Yizhe; Bai, Mingwen; Hall, David; Dou, Rui
ABSTRACT: The sintering behaviours of undoped and 8 mol% B-site Ni-doped Ba0.5 Sr0.5 Co0.8 Fe0.2 O3−δ (BSCF) under various conditions are systematically investigated. Ni doping increases the lattice parameter of BSCF. The grain size of the undoped BSCF increases from 1.52 to 64.8 μm with increasing sintering temperature from 900 at 1150 °C, while the grain size of the Ni-doped counterpart increases from 3.06 to 34.1 μm as the sintering temperature increases from 1000 to 1200 °C. The grain growth kinetics is analysed using the expression D n = tK 0 exp(- Q/RT ). The grain growth exponent n is found to be 3 for the undoped BSCF and 4.7 for the Ni-doped BSCF. The grain growth activation energy (Q) is 650.7±30 kJ/mol for the undoped BSCF and 803.4±37 kJ/mol for the Ni-doped BSCF. This indicates that the Ni dopant has a negative influence on the densification and grain growth of BSCF.